Big data and financial auditing in Portugal - Maldonado, Isabel (2022)
Over time, new instruments have been developed that allow us to collect, store, process and analyse more and more information. However, financial auditors are faced with what is now called the Big Data phenomenon. The objective of this article is to determine the impact that Big Data is having on financial auditing in Portugal and how auditors perceive this new scenario. For this purpose, a questionnaire was prepared and released among Portuguese professional auditors. According to the results obtained, most of the respondents are familiar with the Big Data concept but also consider that the information currently collected is sufficient to support auditing conclusions. These professionals assume that they feel limitations when faced with large amounts of data and that the current tools are not prepared for the analysis of large amounts of data, not to mention Big Data analysis. Regarding the efforts that can be made to increase knowledge of the Big Data in the auditing profession, the great majority are not aware of any professional or complementary training that mentioned the Big Data theme provided by the professional order. Our responses analysis leads to conclude that despite the impact that Big Data is having on society in general, a large number of audit professionals in Portugal are still not prepared to deal with this phenomenon.